2019
DOI: 10.3389/fncel.2019.00433
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Brain Developmental Abnormalities in the Pathogenesis of Juvenile Myoclonic Epilepsy

Abstract: Juvenile myoclonic epilepsy (JME), a lifelong disorder that starts during adolescence, is the most common of genetic generalized epilepsy syndromes. JME is characterized by awakening myoclonic jerks and myoclonic-tonic-clonic (m-t-c) grand mal convulsions. Unfortunately, one third of JME patients have drug refractory m-t-c convulsions and these recur in 70–80% who attempt to stop antiepileptic drugs (AEDs). Behavioral studies documented impulsivity, but also impairment of executive functions relying on organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 204 publications
(258 reference statements)
1
10
0
Order By: Relevance
“…JME is characterized by myoclonic jerks (quick jerks of the arms or legs), GTCSs, and sometimes, absence seizures. Its onset typically begins around adolescence (between 12 and 18 years of age) in otherwise healthy children [ 64 ]. JME affects 5–10% of all cases of epilepsy which constitutes 18% of all cases of GGE [ 65 ].…”
Section: Genetic Studies Of Common Epilepsiesmentioning
confidence: 99%
“…JME is characterized by myoclonic jerks (quick jerks of the arms or legs), GTCSs, and sometimes, absence seizures. Its onset typically begins around adolescence (between 12 and 18 years of age) in otherwise healthy children [ 64 ]. JME affects 5–10% of all cases of epilepsy which constitutes 18% of all cases of GGE [ 65 ].…”
Section: Genetic Studies Of Common Epilepsiesmentioning
confidence: 99%
“…Abnormalities in the hippocampus and parietal cortex usually result in mental disorders such as autism spectrum disorder and neurodegeneration ( 30 ). Previous studies have shown that sevoflurane reduces the protein expression levels of caspase-3 in the fetal brain ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gene PRKCZ was thought to be necessary for regulating axonal differentiation and had been implicated in a variety of processes including cardiac muscle function [19,20] . The gene GABRD encodes the subunit of the GABAA receptors, plays an important role in mammalian brain development, and haploinsufficiency may be responsible for neurologic features [21] .…”
Section: Discussionmentioning
confidence: 99%